PENGARUH TERPAAN BERITA HOAX "KEBAKARAN GUDANG JNE BINTARO" TERHADAP KEPERCAYAAN MASYARAKAT PADA MEDIA ONLINE - Ainun Fadhilah (2020)
The growth of online media caused information to become flooding, that said it also caused information that has been spreaded out to create false information or hoaxes that may harm some entities. The purpose of this research is to get to know the existence of impact of hoax "the fire of JNE Bintaro's warehouse" on people's believe for online media TribunJakarta.com. This research is conducted with quantitative approach. The research method used is survey design with questionnaire for data collecting instrument. The theory used in this research is uses & effect. The sampling technique used is proportionate random sampling. The result of this study shows that t calculation (-6.585) > t table (1.661). Therefore, it can be concluded that Ho is declined and Ha was accepted. By that's being said, there is a significant negative impact on the hoax news "the fire of JNE Bintaro's warehouse" on people's believe for online media TribunJakarta.com. Keywords: Believes, Hoax, News Exposure, Online Media, TribunJakarta.com.